Novel Therapy for Glioblastoma Multiforme by Restoring LRRC4 in Tumor Cells: LRRC4 Inhibits Tumor-Infitrating Regulatory T Cells by Cytokine and Programmed Cell Death 1-Containing Exosomes - Li, Peiyao; Feng, Jianbo; Liu, Yang; Liu, Qiang; Fan, Li; Liu, Qing; She, Xiaoling; Liu, Changhong; Liu, Tao; Zhao, Chunhua; Wang, Wei; Li, Guiyuan; et al. (Frontiers in Immunology, 2017)
Glioblastoma multiforme (GBM) is a heterogeneous malignant brain tumor, the pathological incidence of which induces the accumulation of tumor-infiltrating lymphocytes. As a tumor suppressor gene, LRRC4 is absent in GBM cells. Here, we report that the recovery of LRRC4 in GBM cells inhibited the infiltration of tumor-infiltrating regulatory T cells (Ti-Treg), promoted the expansion of tumor-infiltrating effector T (Ti-Teff) cells and CD4+CCR4+ T cells, and enhanced the chemotaxis of CD4+CCR4+ T cells in the GBM immune microenvironment. LRRC4 was not transferred into tumor-infiltrating lymphocytes from GBM cells through exosomes but mainly exerted its inhibiting function on Ti-Treg cell expansion by directly promoting cytokine secretion. GBM cell-derived exosomes (cytokine-free and PD-1 containing) also contributed to the modulation of LRRC4 on Ti-Treg, Ti-Teff and CD4+CCR4+ T cells. In GBM cells, LRRC4 directly bound to PDPK1, phosphorylated IKKβser181, facilitated NF-κB activation, and promoted the secretion of IL-6, CCL2 and IFN-g. In addition, HSP90 was required to maintain the interaction between LRRC4 and PDPK1. However, the inhibition of Ti-Treg cell expansion and promotion of CD4+CCR4+ T cell chemotaxis by LRRC4 could be blocked by anti-IL-6 antibody or anti-CCL2 antibody, respectively. miR-101 is a suppressor gene in GBM. Our previous studies have shown that EZH2, EED and DNMT3A are direct targets of miR-101. Here we showed that miR-101 reversed the hypermethylation of the LRRC4 promoter and induced the re-expression of LRRC4 in GBM cells by directly targeting EZH2, EED and DNMT3A. Our results reveal a novel mechanism underlying GBM microenvironment and provide a new therapeutic strategy using re-expression of LRRC4 in GBM cells to create a permissive intratumoral environment.